Risk factors and clinical manifestations of choroidal melanoma: An integrative review (Research, Society and Development, 2024)
Uveal melanoma is the most common type of intraocular cancer in adults, and can mostly affect the choroid, which forms the uvea together with the cialial body and the iris. Several risk factors may predispose to this disease, from genetic to occupational conditions. The aim of this article is to investigate and discuss the main risk factors and clinical manifestations presented in choroidal melanoma by the articles selected for the review. This is an integrative literature review, where the databases of the National Library of Medicine National Institutes of Health (PubMed) and Virtual Health Library (VHL) were used for the research. Articles with open online access were selected, written in English or Portuguese, produced between the years 2018 to 2023, with the type of study meta-analysis, systematic review, review and randomized clinical trial, and that answered the guiding question. A total of 4 articles were found to discuss the main risk factors and clinical manifestations of choroidal melanoma.